Investigating the Effect of Viscous Yield Dampers on Concrete Structure Performance - Nima Marzban; Parisa Esmaeiltabar Nesheli (Shock and Vibration)
Viscous dampers are one of the most effective devices in the energy consumption of the buildings. The passive hybrid system progressive applications cause each of the dampers to compensate for the weakness of the other system, thus increasing the efficiency of passive control of the structure. Speed-based viscous dampers will adjust the amount of depreciation force based on the acceleration and velocity entering the system. On the other hand, displacement-based surge dampers adjust the amount of depreciation force based on the displacement required. Therefore, considering the different performances of these two dampers, the effect of using both of them in one structure can be investigated. In this study, by combining these two dampers, the seismic behavior of concrete structures has been evaluated. To study them, 5- and 10-story structures have been designed using FE method and have been subjected to earthquake records. Historical analysis shows that the use of hybrid dampers reduces the amount of seismic input force to the structure and also the amount of floor drift is reduced due to the use of dampers and also the capacity of structures for these structures is increased. The results of the study show that the presence of dampers in the structure increases energy absorption and improves performance in the structure.